Целесообразность использования йодсодержащих препаратов в спорте - Агавни Гиносян; Арег Оганесян; Наири Манукян (ՀՀ ԳԱԱ հրատ.)
Тhe article examines the feasibility of using iodine–containing drugs by athletes under intense physical training to recommend the optimal dosage and pharmaceutical form of iodine for athletes. Comparative analysis showed that the use of “Armenicum” capsule statistically significantly changes the levels of hemoglobin, the red blood cells and lymphocytes, the level of immunoglobulin A. The ratio of testosterone/cortisol, which characterizes the anabolic status of the body, was significantly increased among the athletes taking high doses of iodine.Հոդվածում քննարկվում են յոդ պարունակող դեղերի կիրառման հնարավորութունները ինտենսիվ ֆիզիկական մարզումների ժամանակ՝ օպտիմալ դեղաչափի և դեղաձևի որոշման նպատակով: Համեմատական վերլուծությունը ցույց է տվել, որ «Արմենիկում» դեղապատիճի կիրառումն վիճակագրորեն զգալի փոխում է հեմոգլոբինի, էրիթրոցիտների և լիմֆոցիտների, ինչպես նաև իմունոգլոբուլին Ա–ի մակարդակը: Բարձր դեղաչափ ընդունած մարզիկների մոտ զգալիորեն աճում է տեստոստերոն/ կորտիզոլ հարաբերակցությունը, որը բնութագրում է մարմնի անաբոլիկ վիճակը:
Keywords: Medicine; Sports; Pharmacy and materia medica